Comparing perspectives of family caregivers and healthcare professionals regarding caregiver burden in dementia care: results of a mixed methods study in a rural setting. (26th December 2019) - Krutter, Simon; Schaffler-Schaden, Dagmar; Essl-Maurer, Roland; Wurm, Laura; Seymer, Alexander; Kriechmayr, Celine; Mann, Eva; Osterbrink, Juergen; Flamm, Maria
Abstract: Background: Persons with dementia (PwD) need support to remain in their own homes as long as possible. Family caregivers, homecare nurses and general practitioners (GPs) play an important role in providing this support, particularly in rural settings. Assessing caregiver burden is important to prevent adverse health effects among this population. This study analysed perceived burden and needs of family caregivers of PwD in rural areas from the perspectives of healthcare professionals and family caregivers. Methods: This was a sequential explanatory mixed methods study that used both questionnaires and semi-structured interviews. Questionnaires measuring caregiver burden, quality of life and nursing needs were distributed to the caregivers; health professionals received questionnaires with adjusted items for each group. Additionally, in-depth qualitative interviews were carried out with eight family caregivers. Results: The cross-sectional survey population included GPs ( n = 50), homecare nurses ( n = 140) and family caregivers ( n = 113). Healthcare professionals similarly assessed the psychosocial burden and stress caused by behavioural disturbances as most relevant. Psychological stress, social burden and disruptive behaviour (in that order) were regarded as the most important factors from the caregivers' perspective. It was found that 31% of caregivers reported permanent or frequent caregiver overload. Eight themes related to caregiver burden emerged from the subsequent interviews with caregivers. Conclusions: Professional support at home on an hourly basis was found to be highly relevant to prevent social isolation and compensate for lack of leisure among caregivers of PwD. Improvement of interprofessional dementia-related education is needed to ensure high-quality primary care.